STRATEGI PENGEMBANGAN BISNIS PERUSAHAAN DISTRIBUSI GAS ALAMPADA PELANGGAN KOMERSIAL DI WILAYAH SURABAYA - Eliza Jazilia; Danis Maulana; Ristanti Akseptori (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Natural gas distribution in Indonesia is used to replace the role of LPG which has been used by the community for household activities and commercial industry which has been expanded by the government. As is the case in the Surabaya area, through the Natural Gas Distribution Company, the government is starting to replace the useof LPG Gas with Natural Gas. The purpose of this research is to determine the company's internal and external factors and determine alternative commercial customer business development strategies for the company. The method used is SWOT Analysis (Strengths, Weaknesses, Threats, Opportunities). The tools used to analyze data are the IFE Matrix, EFE Matrix, IE Matrix and SWOT Matrix which are used as research calculation tools. Theresults of this research show that there are 12 internal factors consisting of 8 strengths and 4 weaknesses and 10external factors consisting of 6 opportunities and 4 threats. Weighting on external aspects that are opportunitiesis the LPG scarcity factor and the company's threat is limited network availability. Meanwhile, in internal weighting, the strength is product quality and the weakness is the lack of human resources to carry out the strategy. The results of the analysis show that the company is in cell IV position, which means growth and development andthere are 2 alternative strategies, so the strategies that must be carried out and implemented by the company are market penetration and market development. Market Penetration Strategy is a strategy that aims to increase market share in the same market with more intensive marketing efforts, then Market Development Strategy is a strategy that aims to offer existing products and services to attract new markets or customers.